'I am getting on nicely in the dark': the environments of 'Proteus'. Issue 2 (1st February 2022) - Brazeau, Robert
ABSTRACT: This essay examines the 'Proteus' chapter of Joyce's Ulysses from the standpoint of ecocritical theory, arguing throughout that Joyce salvages a notion of ecological vibrancy from a depleted, near-barren landscape. The essay assumes from the outset that 'Proteus' offers something like proto-work in ecological theory and that Joyce's attention to nature and natural processes are implicated in the diction, grammar, and aesthetic form of the chapter. Analyzing emergent and established concerns of the still evolving discourse of ecocriticism, the essay ultimately argues that Joyce was an early observer of the many ways in which we inhabit nature and it inhabits us.